OPTIMASI EKSTRAKSI SILIKA DAN ALUMINA DARI LUMPUR SIDOARJO - Putra, Ahmad Naufal Hasti Eka; Tjahjanto, Rachmat Triandi; Khunur, Mohammad Misbah (Jurusan Kimia, FMIPA Universitas Brawijaya, 2013)
Optimization of silica and alumina extraction from Sidoarjo mud have studied. The aim of this research is to know the optimum condition of silica and alumina extraction from Sidoarjo mud. Optimum condition of extraction is studied by variying the concentration and solvent used in the extraction process. Hydrochloric acid and NaOH were used in silica and alumina extraction from Sidoarjo mud. Hydrochloric acid was added to the filtrate of NaOH extract to obtain Al(OH)3 at pH 8, further the HCl added until pH 4 to obtain Si(OH)4. The filtrate of HCl extract wad added by NaOH until pH 4 to precipitate Fe(OH)3, further NaOH was added until pH 8 to obtain Al(OH)3. The result of this experiment shows that extractions result was affected by the concentration and the solvent used. The optimal concentration of solvent for extraction prosses is 6 M for both acid and base. The purest silica in this research was obtained from NaOH extract with the purity level of 95,6%.